2018
DOI: 10.3389/fpsyt.2018.00026
|View full text |Cite
|
Sign up to set email alerts
|

Higher Impulsivity As a Distinctive Trait of Severe Cocaine Addiction among Individuals Treated for Cocaine or Alcohol Use Disorders

Abstract: AimsDespite alcohol being the most often used addictive substance among addicted patients, use of other substances such as cocaine has increased over recent years, and the combination of both drugs aggravates health impairment and complicates clinical assessment. The aim of this study is to identify and characterize heterogeneous subgroups of cocaine- and alcohol-addicted patients with common characteristics based on substance use disorders, psychiatric comorbidity and impulsivity.MethodsA total of 214 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 53 publications
1
9
0
2
Order By: Relevance
“…Taking into account the I-PACE model [15,16], it can be assumed that impulsivity is one of the crucial predictors of problematic behaviors. Additionally, many studies point to high impulsivity as one of the essential risk factors of psychoactive substance use [50][51][52] and behavioral addictions [53][54][55][56][57][58]. Previous studies have also indicated that high impulsivity is associated with low life satisfaction [27] and that addictions are also associated with low life satisfaction [59][60][61].…”
Section: Problematic Facebook Use and Problematic Video Gamingmentioning
confidence: 99%
“…Taking into account the I-PACE model [15,16], it can be assumed that impulsivity is one of the crucial predictors of problematic behaviors. Additionally, many studies point to high impulsivity as one of the essential risk factors of psychoactive substance use [50][51][52] and behavioral addictions [53][54][55][56][57][58]. Previous studies have also indicated that high impulsivity is associated with low life satisfaction [27] and that addictions are also associated with low life satisfaction [59][60][61].…”
Section: Problematic Facebook Use and Problematic Video Gamingmentioning
confidence: 99%
“…The role of impulsivity in SUDs is well documented [55,57,58,59,60]. Many studies have reported higher impulsivity levels with increasing substance use across a wide range of questionnaires and behavioural tasks, and for a variety of different substances [61,62,63,64,65,66]. For example, Noël et al [67] performed a series of behavioural tasks assessing the ability to suppress irrelevant responses (response inhibition) and irrelevant information (proactive interference) in a group of detoxified alcohol-dependent individuals and matched healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado está en línea con la literatura previa sobre el tema (Grant et al, 2019;Jo et al, 2018;Kim et al, 2016;Peterka-Bonetta et al, 2019;Wu et al, 2013). Además, este resultado era esperable, ya que la impulsividad se ha relacionado con numerosas adicciones, incluida la adicción a la cocaína (García-Marchena et al, 2018), al alcohol (Shin et al, 2012), a la comida (VanderBroek-Stice et al, 2017), al tabaco (Liu et al, 2019), al sexo (Levi et al, 2020), etc.…”
Section: Discussionunclassified